Effect of itraconazole on the quality of life in patients with moderate to severe seborrheic dermatitis: a randomized, placebo-controlled trial - Zaheer Abbas; Seyede Zahra Ghodsi; Robabeh Abedeni (Mattioli1885, 2016)
Background: Few studies have examined the effect of seborrheic dermatitis (SD) and/or its consequent therapy on a patient's quality of life. Itraconazole has been suggested as an effective therapy for severe SD but its impact on Quality of Life (QoL) in these patients has never been studied before. Objective: The study aimed to verify the efficacy of the itraconazole on the quality of life in patients with moderate to severe SD. Methods: A randomized, double-blind, placebo controlled trial was planned to describe the effect of SD per se on QoL and to determine the impact of oral itraconazole or placebo on QoL of SD patients. Sixty-eight patients with moderate to severe SD participated in the study to receive either itraconazole or placebo. Dermatology Life Quality Index was used to evaluate their quality of life before and after treatment. Itraconazole 200 mg/daily or placebo was prescribed for one week and then the first two days of every month for the following three months. Fifty-seven patients completed the study. Results: Significant improvement was observed in QoL of both itraconazole and placebo groups, but itraconazole group showed significantly higher improvement as compared to placebo (p=0.001). QoL was impaired significantly with high disease severity (p=0.002) and facial involvement (p=0.017). Conclusions: Itraconazole significantly improves the QoL in patients with moderate to severe SD.